History for what? Reflections about the utilities of teaching History in the career of Social Work (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2018)
We present a reflection about our practice as history teachers in the career of Social Work. Since this profession was strongly linked to medicine, and about thirty years ago it made a turn towards the social sciences, we asked ourselves how this relationship is perceived by students, particularly between history and Social Work, with the objective of advancing in better didactic strategies in the construction of historical knowledge. First, we will make a brief historical tour about the development of the profession and the entrance of social sciences for training. Second, we will present the students' considerations about ‘What is the use of studying history in Social Work?’ Finally, we will carry out an analysis that will be the input used for the elaboration of a pedagogical proposal within the framework of the Chair.
Keywords: history; social work; professional training